Pengembangan Aplikasi Kasir Android Bagi Pelaku Usaha Mikro - Edi Wahyudin; Edi Tohidi; Muhamad Yoni Ardiansah; Muhamad Agastya (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The use of Android-based cashier applications can improve the efficiency and accuracy of transactions for micro-entrepreneurs. This Community Partnership Program aims to provide training on creating simple Android-based cashier applications for micro-entrepreneurs. This training covers the introduction to the basics of Android application development using a specific platform, the design of an intuitive user interface (UI) for sales transactions, the implementation of key cashier application features such as transaction recording, calculation of total purchases, and simple report generation. It is expected that, through this training, micro-entrepreneurs can have the ability to create cashier applications that suit their business needs, thereby improving operational efficiency and financial management.